Resilient Ferry Stations - an adaptive approach to the changing cities - Cruz, Patricia-anne V.; De Leon, Ruby Teresa (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Water transportation within Metro Manila suffers from many limitations, failing to adapt to urbanization and the severe effects of climate change, which have impeded its development. Common problems faced by water transportation and waterfront development are the changing water levels and limited usable space, and the lack of activity to bring people to the water. Thus, the constraints of the waterfront have resulted in an underutilized public water transportation system. This thesis aims to improve public water transportation by designing resilient ferry stations that can adapt to the changing transportation needs within Metro Manila and the vulnerabilities present in waterfront development. From the research gathered, the proposed solution is a floating ferry station, specifically an amphibious structure that can rise with the water levels. This includes a modular system which can be replicable to expand the ferry service network. Additional solutions of the project are to provide other functions nearby, such as government services, commercial areas, and recreational parks, to increase activity along the waterfront. The project will serve as a model for improving ferry stations and thereby, creating a more resilient and connected water transportation system in Metro Manila.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Ferries -- Metro Manila; Floating harbors -- Metro Manila